Advancing conventional guidelines in phytotoxicity studies assessing toxicant’s impact on seedling morphology and anatomy - Bárbara S. Diogo; Sara Rodrigues; Sara C. Antunes (Scientific Reports)
Abstract Studies on plant ecotoxicology focus essentially on growth and biochemical processes, often overlooking anatomical and morphological alterations that may occur post-germination. These changes, however, offer valuable insights into early environmental stress, enabling proactive intervention and mitigation strategies. Thus, this study aimed to identify and characterize morphological and anatomical alterations during early seedlings’ development, using a new Visual PhytoToxicity assessment (ViPTox) approach. This visual scoring system categorizes the alterations recorded into severity levels, offering a simple, reproducible method for assessing phytotoxicity based on observable changes in plant structure. A standard germination assay with Lactuca sativa was conducted using potassium dichromate (PD, reference compound) at 0.00, 100.5, 120.6, 144.7, 173.6, 208.3, and 250.0 mg/L. Standard endpoints, including germination rate, seedling size, and fresh and dry weight were evaluated alongside a novel ecotoxicological approach. Based on the seedling effects observed, a dichotomous key with a scoring system was defined using a classification range from 0 (normal seedling) to 10 (no germination - maximum damage), providing insights into the severity of observed alterations (e.g., absence of roots and/or leaves (score 9), chlorosis and necrosis (score 8), atrophy (score 7, 6, and 5), deformations (score 4 and 3), reduction of size (score 2 and 1)), in order to calculate the phyto-morphological damage (PMD). Considering the standard endpoints, no significant alterations were observed in L. sativa germination. However, a significant decrease in seedling size (> 20 %) and fresh weight (> 50 %) was observed, after exposure to the highest PD concentrations (173.6, 208.3, and 250.0 mg/L). Regarding the ViPTox approach, PMD was observed in all concentrations ≥ 120.6 mg/L of PD. Significant effects were observed even at lower PD concentrations (120.6 and 144.7 mg/L) where phyto-morphological damages (e.g., atrophy and deformations) were quantified, while standard endpoints were unaffected. ViPTox presents a reproducible, non-invasive, and cost-effective approach to evaluate seedling responses to environmental stress, complementing traditional assessment techniques while providing crucial insights that support proactive intervention and effective mitigation strategies.